Effectiveness of Cognitive Behavioral Group Counseling to Increase Self-Confident of Vocational High School Students - Apriliana, I Putu Agus; Suranata, Kadek (Bisma The Journal of Counseling, 2020)
Low student self-confident will affect to the his/her development process in school. The purpose of this study is to determine the effectiveness of cognitive behavioral group counseling to increase self-confident of vocational high school students. The research design is one group pre-test – post-test design. The population is student’s X grade class at SMK Prshanti Nilayam Kuta. Determination of the sample using purposive sampling technique, in order to get 8 students as the sample. The data analysis using t-test. The results of this study showed that self-confident score was an increase after join in the group counseling activities. The results of hypothesis testing show that the value of t = 7,434 with a significance of 0.000 (<0.05) so that null hypothesis is rejected. These results indicate that group counseling with cognitive behavioral approach is effective to increase self-confident of vocational high school students.